Fragmentos de visualidades chinesas no setecentos mineiro(1920-1970) - Andrea Piazzaroli Longobardi (2011)
This dissertation attempts to outline practices and values linked to the gender of chinoiserie in the context of sacred ornaments of the Minas Gerais Province (1712-1770). In outlining the history of painting with vermilion pigment techniques, it was realized that the pigment was tied to oriental themes as long as the circulation of objects from the East Indies was increased, as well as the spread of Oriental taste. The propagation of the Oriental taste was marked by the appreciation of Eastern goods, and by the projection of a land full of wonders and harmoniums idea on to kingdoms and empires in the Far East. The chinoiserie studied by this work make reference to a specific Sinic genre of art - the shanshui (mountain-water). This genre was widespread in Europe through the circulation of ornate porcelains. Following the shanshui structure and composition, the European art combined exotic images that circulated though European ornamentalists painters. This superposition of models and signs is a feature that is in full agreement with the rhetorical mode of production and invention of coeval arts. In order to ascertain the composition patterns and the references used in the Minas Gerais Province´s chinesices ,this research made a list of images found on these panels. Were analyzed, for this purpose, specific examples, like the left door of the Igreja Matriz de Nossa Senhora da Conceição (Sabará) and the Igreja de Nossa Senhora da Expectaçção do Parto (Sabará). It is observed that, on the production of the chinoiserie, European artists had employed techniques based their ingenuity on fantasy more than sense - both ways of composing characteristics of eighteenth and seventeenth-century art. Thus, both gold lacquer and gilding, as well as the exotic chinesices signs, can be seen as a reference that appear due to the spectator´s affects commotion. It is inferred that the ornament in the eighteenth century Iberian art can be seen as enkomion, or praise of valuable things. So, the shape and composition of the invention of chinoiserie genre can be defined - as the historian Alvaro Samuel - as "orientalist exotic practices." The otherness and the exotic, on these works, indicate the projection of Western culture's own dreams and expectations on this genre production.